In vivo rescue of recombinant Zika virus from an infectious cDNA clone and its implications in vaccine development - Ávila-Pérez, Gines (Sci Rep, 2020)
Zika virus (ZIKV) is a mosquito-borne member of the Flaviviridae family that has been known to circulate for decades causing mild febrile illness. The more recent ZIKV outbreaks in the Americas and the Caribbean associated with congenital malformations and Guillain-Barré syndrome in adults have placed public health officials in high alert and highlight the significant impact of ZIKV on human health. New technologies to study the biology of ZIKV and to develop more effective prevention options are highly desired. In this study we demonstrate that direct delivery in mice of an infectious ZIKV cDNA clone allows the rescue of recombinant (r)ZIKV in vivo. A bacterial artificial chromosome containing the sequence of ZIKV strain Paraiba/2015 under the control of the cytomegalovirus promoter was complexed with a commercial transfection reagent and administrated using different routes in type-I interferon receptor deficient A129 mice. Clinical signs and death associated with ZIKV viremia were observed in mice. The rZIKV recovered from these mice remained fully virulent in a second passage in mice. Interestingly, infectious rZIKV was also recovered after intraperitoneal inoculation of the rZIKV cDNA in the absence of transfection reagent. Further expanding these studies, we demonstrate that a single intraperitoneal inoculation of a cDNA clone encoding an attenuated rZIKV was safe, highly immunogenic, and provided full protection against lethal ZIKV challenge. This novel in vivo reverse genetics method is a potentially suitable delivery platform for the study of wild-type and live-attenuated ZIKV devoid of confounding factors typical associated with in vitro systems. Moreover, our results open the possibility of employing similar in vivo reverse genetic approaches for the generation of other viruses and, therefore, change the way we will use reverse genetics in the future.